Activated Glia Increased the Level of Proinflammatory Cytokines in a Resiniferatoxin-Induced Neuropathic Pain Rat Model. Issue 6 (November 2016) - Lei, Yishan; Sun, Yu'e; Lu, Cui'e; Ma, Zhengliang; Gu, Xiaoping
Abstract : Background and Objectives: Administration of resiniferatoxin (RTX) can mimic the clinical symptoms of postherpetic neuralgia. However, it is unclear whether activated glia contribute to the pathogenesis of RTX-induced neuropathic pain; furthermore, the relationship between p38, N -methyl-D-aspartate receptor type 2B (NR2B) as well as proinflammatory cytokines and activated glia remains unknown. Methods: Intraperitoneal injection of RTX was performed to induce neuropathic pain in rats. Mechanical allodynia and thermal hyperalgesia were assessed by von Frey filaments and a radiant heat stimulus, respectively. Western blot and immunofluorescence labeling examined the expression of NR2B, activated glia markers, p38, and proinflammatory cytokines in the spinal cord. We further investigated the effect of the glial inhibitors, fluorocitrate and minocycline, on nociceptive behaviors and expression of p38, NR2B, and proinflammatory cytokines. Results: Resiniferatoxin leads to an increase of paw withdrawal latency to a heat stimulus and caused a mechanical allodynia within 2 weeks. The expression of tumor necrosis factor α, IL-1β, p38, and NR2B was up-regulated in RTX-induced neuropathic pain rat model and lasted for at least 49 days. Microglia were activated at the early phase of the disease, whereas activated astrocytes were detected in the sustainment phase. Both minocycline and fluorocitrate attenuated the nociceptive behaviors and expression of related proteins. Conclusions: Activated glia participate in the pathogenesis of RTX-induced neuropathic pain and are likely to be the source of proinflammatory cytokines. Inhibition of glia contributes to an analgesic effect. These findings provide a novel strategy for the treatment of postherpetic neuralgia.